CrawNet: Multimedia Crawler Resources for Both Surface and Hidden Web - Pech-May, Fernando; Martínez-Rebollar, Alicia; Estrada-Esquivel, Hugo; Pedroza-Landa, Eduardo (Lámpsakos (revista descontinuada), 2015)
The web is the most used information source in both academic, scientific and industry forums. Its explosive growth has generated billions of pages with information which may be categorized as surface web, composed of static pages that are indexed into a hidden web, accessible through search templates. This paper presents the development of a crawler that allows searching, queries, and analysis of information in the surface web and hidden in specific domains of the web.